2016
DOI: 10.1364/oe.24.028889
|View full text |Cite
|
Sign up to set email alerts
|

Modeling framework for piezoelectrically actuated MEMS tunable lenses

Abstract: WWe report a modeling framework for evaluating the performance of piezoelectrically actuated MEMS tunable lenses. It models the static opto-electromechanical coupling for symmetric configurations of piezoelectric actuators based on the laminated-plate theory, linear piezoelectricity, and ray tracing. With these assumptions, it helps to find geometrical parameters for actuators on clamped square or circular diaphragms that give a diffraction-limited tunable lens with minimum F-number. The tunable lens' optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…For case 6, with all γ values of interest, we have previously found that N ¼ 28 is sufficient to obtain less than 10% l 2 relative error norm when comparing the displacement from the variational solution against FEM. 15 This observation still holds for the other polygonal-shaped pupils.…”
Section: Variational Formulation and Its Solutionsmentioning
confidence: 81%
See 4 more Smart Citations
“…For case 6, with all γ values of interest, we have previously found that N ¼ 28 is sufficient to obtain less than 10% l 2 relative error norm when comparing the displacement from the variational solution against FEM. 15 This observation still holds for the other polygonal-shaped pupils.…”
Section: Variational Formulation and Its Solutionsmentioning
confidence: 81%
“…In a previous research work, 15 we have developed a variational formulation based on the classical laminated plate theory, linear piezoelectricity, quasielectrostatic conditions, and a thin film approximation. Originally, it was used to predict the displacement profile of the transparent membrane in case 6 [refer to Fig.…”
Section: Variational Formulation and Its Solutionsmentioning
confidence: 99%
See 3 more Smart Citations